2014
DOI: 10.1002/uog.13231
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fetal cardiomyopathy in early‐stage twin–twin transfusion syndrome: comparison between commonly reported cardiovascular assessment scores

Abstract: Objectives To assess the relationship between commonly reported fetal cardiomyopathy scoring systems in earlystage twin-twin transfusion syndrome (TTTS). Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…This is in line with previous studies that have reported signs of systolic and diastolic dysfunction in recipient twins including TTTS stages I and II [13, 14, 20-22]. These echocardiographic findings can be in part due to an increased preload.…”
Section: Discussionsupporting
confidence: 81%
“…This is in line with previous studies that have reported signs of systolic and diastolic dysfunction in recipient twins including TTTS stages I and II [13, 14, 20-22]. These echocardiographic findings can be in part due to an increased preload.…”
Section: Discussionsupporting
confidence: 81%
“…The increases in ICT and IRT but not ET can be interpreted as myocardial impairment of both contraction and relaxation with shortening of the diastolic filling time. Although several studies have evaluated cardiac dysfunction in recipients using Mod‐MPI, only a few reports have assessed its components, mainly focusing on the diastolic function . Divanović et al reported increased IRT in recipients, and this change was more significant in advanced‐stage TTTS .…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that, similar to previously reported studies, [4][5][6][7][8] intra-observer variability and inter-observer variability are low and agreement is within acceptable limits for the majority of quantitative It is somewhat surprising that the Doppler MPI is so variable between testers, particularly given our center's substantial experience in the measurement of MPI in fetuses. [12][13][14][15] Studies have reported different ways to measure the variables necessary to calculate the MPI. 5,[16][17][18] We utilize the valve click method for MPI assessment, as it has previously been reported to lower variation.…”
Section: Discussionmentioning
confidence: 99%
“…ment. It is somewhat surprising that the Doppler MPI is so variable between testers, particularly given our center's substantial experience in the measurement of MPI in fetuses [12][13][14][15]. In comparison, the intra-observer percent mean difference and inter-observer percent mean difference were all <10% (with the exception of pulmonary vein VTI).…”
mentioning
confidence: 96%